2013
DOI: 10.1210/me.2012-1219
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Role of Sertoli Cell Androgen Receptor Expression in Spermatogenic Development

Abstract: Sertoli cell (SC) androgen receptor (AR) activity is vital for spermatogenesis. We created a unique gain-of-function transgenic (Tg) mouse model to determine the temporal role of SCAR expression in testicular development. The SC-specific rat Abpa promoter directed human Tg AR [Tg SC-specific AR (TgSCAR)] expression, providing strong premature postnatal AR immunolocalized to SC nuclei. Independent Tg lines revealed that TgSCAR dose dependently reduced postnatal and mature testis size (to 60% normal), whereas an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
64
1
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 64 publications
0
64
1
6
Order By: Relevance
“…Testosterone generally seems to have a minor role in spermatogonial proliferation [16,17] but is involved in the survival of spermatocytes and spermatids, presumably through anti-apoptotic mechanisms [18]. On the other hand, Hazra et al developed transgenic gain-of-function Sertoli cell-specific AR mice and observed premature postnatal spermatogenic development with increased levels of post-meiotic germ cells [19]. These findings are very important in the clinical setting because we can increase ITT by using hCG, clomiphene citrate or aromatase inhibitors.…”
Section: Leydig Cell-derived Growth Factorsmentioning
confidence: 99%
“…Testosterone generally seems to have a minor role in spermatogonial proliferation [16,17] but is involved in the survival of spermatocytes and spermatids, presumably through anti-apoptotic mechanisms [18]. On the other hand, Hazra et al developed transgenic gain-of-function Sertoli cell-specific AR mice and observed premature postnatal spermatogenic development with increased levels of post-meiotic germ cells [19]. These findings are very important in the clinical setting because we can increase ITT by using hCG, clomiphene citrate or aromatase inhibitors.…”
Section: Leydig Cell-derived Growth Factorsmentioning
confidence: 99%
“…Это связано с тем, что тестостерон тормозит пролиферацию клеток Сертоли, стимулирует их диффе-ренцировку, формирование битестикулярного барьера и начало сперматогенеза (Escott et al, 2014). Мутантные мыши TgSCAR, для которых характерна преждевремен-ная обильная экспрессия андрогенового рецептора на клетках Сертоли, характеризуются более ранним началом сперматогенеза, но и меньшим размером семенников во взрослом возрасте по сравнению с мышами дикого типа (Hazra et al, 2013).…”
Section: Discussionunclassified
“…Секреция тестосте-рона относительно высока в первые сутки после родов, но затем снижается и начинает вновь увеличиваться в нача ле полового созревания (Chen et al, 2015). Увеличение се-креции тестостерона в перинатальный период и во вре-мя полового созревания оказывает программирующий эф-фект на развитие мозговых структур, контролирующих поведение (Trainor et al, 2009), а также необходимо для развития клеток Сертоли и становления сперматогенеза (Hazra et al, 2013). Ранее было установлено смещение пе-ринатального пика тестостерона у крыс линии ГК на более поздние сроки онтогенеза по сравнению с крысами Вистар (Осадчук, Алехина, 2018).…”
unclassified
“…Furthermore, TgSCAR coordinated the postnatal/pubertal development and testicular capacity of Leydig cells, demonstrating the intimate relationship between the androgen-responsive Sertoli and androgen-producing Leydig cells (11). Independent Tg lines revealed that TgSCAR induced a dose-dependent reduction in postnatal and adult testis size, reflecting precocious Sertoli cell maturation, resulting in a reduced Sertoli cell population, which is thought to largely define the testicular germ cell-carrying capacity, as well as reduced Leydig cell numbers (10,11). Our initial work found that TgSCAR expression had no marked impact upon male fertility.…”
mentioning
confidence: 95%
“…Recently, we created the first gain-of-function transgenic (Tg) model to determine SCAR actions in vivo (10). TgSCAR expression directly showed that the developmental onset of SCAR activity regulates temporal Sertoli cell maturation and postnatal meiotic-postmeiotic germ cell development (11).…”
mentioning
confidence: 99%